STRATEGI PEMBERDAYAAN MASYARAKAT DI KELURAHAN MANGUNHARJO MELALUI PROGRAM PNPM MANDIRI - Bhanu Prawirasworo; Tri Yuniningsih; Maesaroh Maesaroh (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2013)
This research is motivated by problems - problems that occurred in the Village Mangunharjo Semarang, such as the level of welfare of society. The purpose of this study to describe the strategy in an effort to optimize public welfare. In answer to the problem and the purpose of this study, the authors used the theory of empowerment and strategic prencanaan using descriptive qualitative research methods. In collecting the data, the writer uses tehnique through interviews, observation. The informants were selected include: urban employees and the people of community. The results showed the results of the existing planning. Recommended in this research to increase the number of human resources so that the service provided to the community becomes optimal